Estudo de métodos empregando extração em fase sólida e análise por HPLC-DAD e GC-ECD para a determinação de resíduos de pesticidas em águas e da degradação a campo - Kurz, Marcia Helena Scherer (2007)
The culture of irrigated rice generates a great impact to the environment, both in the amount and the quality of waters. In this study, a methodology was developed and validated for the determination, in waters, of residues of the herbicides imazethapyr, bispiribac-sodium and pyrazosulfurom ethyl and of the fipronil insecticide, including its main metabolites: desulfynil, sulfide and sulfone. The herbicides were determined by High Performance Liquid Chromatography with Diode Array Detection (HPLC-DAD), using a mobile phase of acetonitrile:water (55:45, v/v) and a stationary phase of Phenomenex C18. Fipronil and its metabolites were determined by Gas Chromatography with Electron Capture Detection (GC-ECD) using a DB-5 apolar column. For the pre-concentration of the samples, a solid phase extraction (SPE) with C18 cartridges of 500 mg was used. The herbicides were eluted with dichloromethane:methanol (65: 35, v/v) and fipronil and its metabolites were eluted with hexan:isopropanol (3:1, v/v). The parameters of validation of the method include analytical curve, linearity, limits of detection (LOD) and of quantification (LOQ), precision in terms of repetitivity and intermediate precision and accuracy (recovery). All the analytical curves presented r2 values > that 0.9949. The LOQs for the method, considering the 200-fold pre-concentration step, were 0.5, 0.0125 and 0.005 μg L-1 for herbicides, fipronil and its metabolites, respectively. The recoveries were between 90.8 and 114.2%, with RSDs lower than 13.4% for the herbicides, and between 81.3 and 112.3 %, with RSDs lower than 14.2% for fipronil and metabolites. The methodology was applied in a degradation study in irrigated rice farming, in which the individual pesticides had been applied in the harvests of 2004/05 and 2005/06. Residues of imazethapyr were found up to 28 days after its application, and those of bispyribac-sodium and pyrazosulfurom ethyl were found after up to 35 days. Also it was possible to observe the fast degradation of the fipronil insecticide and the consequent formation and degradation of its metabolites. Of the metabolites, fipronil desulfynil presented the greatest concentrations during the study. The method proved to be adequate for the analysis of pesticides in waters and all the validation parameters were within the limits suggested for validation of chromatographic methods.